Texture effects in TiB2 coatings electrodeposited from a NaCl-KCl-K2TiF6-NaF-NaBF4 melt at 700 °c - Krendelsberger R.; Souto M.F.; Sytchev J.; Besenhard J.O.; Fafilek G.; Kronberger H.; Nauer G.E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
TiB2 layers have been electrodeposited on steel and molybdenum substrates from a molten salt electrolyte at 700 °C by either direct current (DC) or pulsed plating techniques. The crystallographic textures of the coatings obtained are described and discussed.